An exploratory study on counterfactual thinking in amyotrophic lateral sclerosis - Poletti, Barbara; Aiello, Edoardo Nicolò; Tagini, Sofia; Solca, Federica; Torre, Silvia; Colombo, Eleonora; Maranzano, Alessio; Bonetti, Ruggero; Schevegher, Francesco; Morelli, Claudia; Doretti, Alberto; Verde, Federico; et al. (Frontiers in Psychology, 2023)
Objectives. This study aimed at exploring 1) the motor and non-motor correlates of counterfactual thinking (CFT) abilities in non-demented amyotrophic lateral sclerosis (ALS) patients, as well as 2) the ability of CFT measures to discriminate these patients from healthy controls (HCs) and patients with vs. without cognitive impairment.Methods. N=110 ALS patients and N=51 HCs were administered two CFT taskswhose sum, resulting in a CFT Index (CFTI), was addressed as the outcome. Patients further underwent an in-depth cognitive, behavioural and motor-functional evaluation. Correlational analyses were run to explore the correlates of the CFTI in patients. Logistic regressions were performed to test whether the CFTI could discriminate patients from HCs.Results. The CFTI was selectively associated (p≤.005) with Fluency and Memory subscales of the Edinburgh Cognitive and Behavioural ALS Screen (ECAS), whilst not with other variables. CFTI scores discriminated patients from HCs (p<.001) with high accuracy (82%), but not patient with a normal vs. a defective performance on the ECAS-Total.CFT measures in non-demented ALS patients are associated with verbal fluency and memory functions, being also able to discriminate them from HCs.